11=4(x-1)-x

Simple and best practice solution for 11=4(x-1)-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11=4(x-1)-x equation:


Simplifying
11 = 4(x + -1) + -1x

Reorder the terms:
11 = 4(-1 + x) + -1x
11 = (-1 * 4 + x * 4) + -1x
11 = (-4 + 4x) + -1x

Combine like terms: 4x + -1x = 3x
11 = -4 + 3x

Solving
11 = -4 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
11 + -3x = -4 + 3x + -3x

Combine like terms: 3x + -3x = 0
11 + -3x = -4 + 0
11 + -3x = -4

Add '-11' to each side of the equation.
11 + -11 + -3x = -4 + -11

Combine like terms: 11 + -11 = 0
0 + -3x = -4 + -11
-3x = -4 + -11

Combine like terms: -4 + -11 = -15
-3x = -15

Divide each side by '-3'.
x = 5

Simplifying
x = 5

See similar equations:

| 2600=(2x-6)m+(x+3)m | | 4x+5=16x+8-12x-3 | | 1.8x+2.8=2.5*2.1 | | -108=3(4+8n) | | 2[4x+1]+5=19 | | (8x-12)(5x-25)=0 | | (a)3.43x=5.6 | | 2[4x+1]5=19 | | 7(y-3)=4y-33 | | 25=3+9x | | 2+.142x=9 | | 3b-2=14 | | 2a-7=4(3a+1)-2 | | -6x-x+10=16-7x-5 | | 3x-5(x-5)=-7+4x-16 | | (-3)(-2)+(-2)(4)= | | 12+5x=-2x-11 | | 13=1-7x-5x | | X^2-15x-1000=0 | | (7y+x)=4 | | y=3x^3+27x^2 | | 8(x+4)=7(2x+3) | | 5(x-4)-3(x-2)=12 | | 2a-17=21 | | 0.22(x+9)=0.2x+3.6 | | =(2x)(3x+1) | | -2w+8-2w=-w-7w+3w | | 0=(2x)(3x+1) | | 39.95+.35m=69.70 | | 2x+3x=2x-4 | | -8-(12-16)= | | 7a-(3a-4)=16 |

Equations solver categories